Sea Cucumber-Based Hydroxyapatite-Chitosan Ameliorate Serum Liver Enzymes and Cytokine Levels in Albino Rats with Femoral Bone Defect - Faisal Fikri; Agus Purnomo; Shekhar Chhetri; Muhammad Thohawi Elziyad Purnama (The Indian Veterinary Journal, 2023)
This study aimed to evaluate sea cucumber-based hydroxyapatite-chitosan (HA-Ch) as a bone graft in cases of bone defects on the variables of serum liver enzymes, IL-4, IL-6, calcium and phosphate levels. A total of 18 albino rats were used in the study, grouped into (C) control group, (T1) polyethylene glycol (PEG) group, and (T2) HA-Ch group. The treatment was carried out for 42 days, respectively. Surgical procedures and modeling of bone defects were carried out using standard methods. Data analyzed statistically using one-way ANOVA followed by post hoc Tukey multiple comparisons test (p